2011
DOI: 10.1002/cncr.26126
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive chromosomal instability patterns in oral verrucous and squamous cell carcinomas detected by high‐resolution DNA flow cytometry

Abstract: BACKGROUND: Oral verrucous carcinomas (OVCs) are characterized by better prognosis than oral squamous cell carcinomas (OSCCs). Because chromosomal instability (CIN) in solid tumors is indicative of prognosis, this study investigated whether OVCs and OSCCs were characterized by differences in CIN biomarkers. METHODS: Fresh or frozen multiple tissue samples were submitted to high-resolution DNA flow cytometry (hr DNA-FCM). RESULTS: DNA aneuploid sublines were detected in 6 of 9 OVCs (66.7%) and in 20 of 25 OSCCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…High DNA aneuploid sublines were predominant (67%) for the OSCCs, which were in addition characterized by the presence of multiple DNA aneuploid sublines in 52% of the DNA aneuploid cases. In contrast, OVCs were characterized by DNA near-diploid aneuploid sublines in 67% of the cases in agreement with previously published data (Pentenero et al, 2011). Overall, the present data support a previous model of aneuploidy genesis and evolution (Giaretti, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…High DNA aneuploid sublines were predominant (67%) for the OSCCs, which were in addition characterized by the presence of multiple DNA aneuploid sublines in 52% of the DNA aneuploid cases. In contrast, OVCs were characterized by DNA near-diploid aneuploid sublines in 67% of the cases in agreement with previously published data (Pentenero et al, 2011). Overall, the present data support a previous model of aneuploidy genesis and evolution (Giaretti, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Another interesting aspect is the development of VC in PVL. VC is a rare histological type, involving only 2–10% of oral carcinomas, which, conversely, are more often observed in patients with PVL …”
Section: Discussionmentioning
confidence: 99%
“…OVC has some pathological similarities to OSCC, especially for well-differentiated OSCC and OVC. Aiming at assessing and validating biomarkers for better understanding of the genesis and molecular mechanisms of OVC and OSCC, Pentenero et al (84) found OVC and OSCC could be differently characterized using chromosomal instability biomarkers. The difference in aggressiveness and prognosis of OVC and OSCC was reflected by DNA index characteristics.…”
Section: Ovc and Oral Squamous Papilloma (Osp)mentioning
confidence: 99%